Avaliação da bioimpedância em recém nascidos pré-termos com síndrome do desconforto respiratório - Calixto, Soraia Zacharias (2005)
The objective of this work is to offer a new method of evaluation using the corporal and thoracic bioimpedance of pre-term neonate with Respiratory Discomfort Syndrome, submitted or not to the invasive mechanical ventilation. Thirty pre-term neonates with Respiratory Discomfort Syndrome were evaluated. They were admitted interned in the newborn intensive therapy unit of Hospital Universitário Evangélico de Curitiba (HUEC) from August to November of 2004. The percentage average of the gestational age in both groups was 32 weeks and the weight was 1250g. The newborn were divided into two groups, group A (15 newborns), with Respiratory Discomfort Syndrome of medium to moderate clinical repercussion, needing the invasive ventilator support. Group B (15 newborn) with light level of Respiratory Discomfort, without the need of ventilator support. The newborn of both groups were evaluated according to the Silverman-Andersen report. Which average in group A was 7 and in group B was 3. Five time speed measurement of subjects of group A were analyzed in the statistical analyses, and they were compared to an unique observation of group B. On the first measurement made in group A, it was noticed a low resistance both corporal (410) and thoracic (32,53) relative to group B. where the percentage average was 595 in the corporal resistance and 46,13 in the thoracic one. In the capacitive reactance it was noticed in the first analyses an inversely proportional behavior, and an increasing in the capacitive reactance for both corporal and thoracic in group A related to group B. As long as the newborns in group A improved clinically, a tendency in increasing the resistance values both corporal and thoracic was observed, correlating with the ventilator support removal. The opposite occurred in the capacitive reactance, both corporal and thoracic. So, the evaluation through the corporal bioimpedance in this work got statistically significant results, and it can be used as a method of evaluation improving the clinical diagnosis of the patient.